Scendere in piazza, scendere in campo. Usi politici e occupazioni simboliche degli spazi urbani tra Belle Époque e fascismo - Giovanni Sbordone (Laboratoire Italien)
At the beginning of the 20th century, italian squares became the scene for a new kind of politics: the stage of socialist and working class crowds. In Venice, this is not the case of St. Mark square, of course: the glorious Piazza is reserved to institutional celebrations. It’s in the smaller campi of popular quarters that common people discover outdoor meeting and political participation. But soon patriotic students and nationalists change the rules, imposing new political uses of public spaces and – finally – fascist squads prevail over choreographic crowds.